Nanoemulsion loaded with marigold flower extract (Tagetes Erecta linn) in gel preparation as anti-wrinkles cosmeceutical - Pimporn Leelapornpisid (2018)
Objective: Aging process causes the skin problems that can be prevented by using effective cosmeceuticals with antioxidant activity. Our previous study demonstrated that ethyl acetate marigold flower extract (EA) consisting the flavonoids that exhibited potent antioxidant activity with safe. Therefore, the EA loaded nanoemulsion was prepared and incorporated into a gel base for anti-wrinkles purpose. Methods: The gel containing nanoemulsion loaded with EA (EANG) was investigated physical properties and antioxidant activity (DPPH assay) at before and after various storage conditions for 3 months. The in vitro skin permeation study was also carried out. Skin irritation test, clinical evaluation for skin moisturizing effect and skin wrinkles-reducing capability were finally performed in thirty healthy human volunteers for 8 weeks. Results: The results showed that the EANG was physically stable and exhibited good stability in antioxidant activity after various storage conditions. From the in vitro permeation test, a major compound: quercetagetin in the EANG was mostly remained in stratum corneum, viable epidermis and dermis rather than in blood circulation which was related to cosmetic purpose. The results from clinical evaluation revealed that the skin hydration was significantly increased after using the EANG. In addition, it showed significant reduction in all wrinkle parameters (surface, volume, Ra and Rz). The percentages of efficiency between EANG area and placebo area were also significantly different in terms of volume, Ra and Rz. Conclusion: Our results strongly indicated that the gel containing nanoemulsion loaded with marigold flower extract was a promising anti-wrinkles cosmeceutical.